Kinerja Keuangan Dan Nilai Perusahaan: Peran Ukuran Perusahaan Perbankan Konvensional Di BEI - Ikhwan; Syamsul Ridjal; La Ode Sumail (Jurnal Ekonomi, 2021)
This study investigates the relationship between BOPO and NPL with financial performance (ROA) and the impact on firm value using signalling theory analysis. In addition, what is also to be achieved is to investigate the role of firm size as a moderating variable and a mediating variable. The research sample was 16 banks that met the criteria (purposive sampling) with 80 observations. BOPO and NPL can be suppressed so as to encourage ROA. Furthermore, ROA can drive TQ. SIZE can strengthen ROA so that TQ becomes high in the market. In addition, ROA is able to push SIZE. And SIZE is able to contribute to TQ. SIZE has a positive and significant role in mediating ROA and TQ.